Social Security: an evaluation of current problems and proposed solutions - Lensing, Daniel Paul (Kansas State University, 2014)
This paper examines several different issues which could make the various Social Security programs insolvent. I evaluate each cause and how it is related to the problems experienced by each program to determine potential policy changes. I draw the majority of my data and information from peer-reviewed scholarly articles, as well as government agencies such as the Social Security Administration, Bureau of Labor Statistics, and the Congressional Research Service. Section 1 of the paper explains the history of the Social Security program and the circumstances creating it. Section 2 goes into greater detail explaining different issues which could make the system insolvent. These areas are: earnings inequality, changes in healthcare, increased life expectancy, changes in the dependency ratio, general trust fund issues, disability trust fund issues, political climate, and recessions/reduced earnings. In Section 3, I evaluate two different proposed plans to fix Social Security. The first plan is an academic plan, the Diamond-Orszag Plan; the second is a plan created by a think-tank, The Heritage Plan. Section 4 gives a conclusion of the implications of the paper and explains the benefits and drawbacks of the two evaluated plans. After evaluating all the problems with Social Security and the two proposed plans, I come to the conclusion that neither plan would be ideal by itself. The Diamond-Orszag Plan is the most politically feasible plan, as it doesn’t change the framework of the current program. A combination of the two plans would be most beneficial, as The Heritage Plan has policy specifically targeting the problems with the Medicare system, where the Diamond-Orszag Plan does not. The three different plans for changing the disability system I evaluate in Section 2.5 are specific, targeted plans and could be a nice addition to a plan such as the Diamond-Orszag Plan. In any case, the sooner politicians finally start taking Social Security’s instability seriously, the better. The longer we wait, the more complex and difficult the problem will become.
Keywords: Social Security; Evaluation of problems; Disability trust fund; Economics (0501); Economics, Finance (0508)